Then we can evaluate the update term by solving the system
@f{eqnarray*}
-\nabla F(\textbf{x}^{k}) \delta \textbf{x}^{k} = -F(\textbf{x}^{k}).
+ \nabla F(\textbf{x}^{k}) \delta \textbf{x}^{k} = -F(\textbf{x}^{k}).
@f}
Here, the left of the previous equation represents the
directional gradient of $F(\textbf{x})$ along $\delta
@f{eqnarray*}
& &\nabla F(\mathbf{u}^{k}, p^{k}) (\delta \mathbf{u}^{k}, \delta p^{k}) \\
\\
- &=& \lim_{\epsilon \to 0} \frac{1}{\epsilon} (F(\mathbf{u}^{k}+\epsilon \delta \mathbf{u}^{k}, p^{k}+\epsilon\nabla\delta p^{k}) - (F(\mathbf{u}^{k}, p^{k}))\\
+ &=& \lim_{\epsilon \to 0} \frac{1}{\epsilon}
+ \left(
+ F(\mathbf{u}^{k} + \epsilon \delta \mathbf{u}^{k},
+ p^{k} + \epsilon \nabla \delta p^{k})
+ - F(\mathbf{u}^{k}, p^{k})
+ \right)\\
+ \\
+ &=& \lim_{\epsilon \to 0} \frac{1}{\epsilon}
+ \left(
+ \begin{array}{c}
+ - \epsilon \nu \Delta \delta \mathbf{u}^{k}
+ + \epsilon \mathbf{u}^{k} \cdot \nabla \delta \mathbf{u}^{k}
+ + \epsilon \delta \mathbf{u}^{k} \cdot \nabla \mathbf{u}^{k}
+ + \epsilon^{2} \delta \mathbf{u}^{k} \cdot \nabla \delta \mathbf{u}^{k}
+ + \epsilon \nabla \delta p^{k}\\
+ - \epsilon \nabla \cdot \delta \mathbf{u}^{k}\\
+ \end{array}
+ \right)\\
\\
- &=& \lim_{\epsilon \to 0} \frac{1}{\epsilon} \left(
- \begin{array}{c}
- - \epsilon\nu\Delta\delta \mathbf{u}^{k} + \epsilon\mathbf{u}^{k}\cdot\nabla\delta\mathbf{u}^{k}+\epsilon\delta\mathbf{u}^{k}\cdot\nabla\mathbf{u}^{k}+\epsilon^{2}\delta\mathbf{u}^{k}\cdot\nabla\delta\mathbf{u}^{k}+\epsilon \nabla\delta p^{k}\\
- - \epsilon \nabla \cdot\delta \mathbf{u}^{k}\\
- \end{array}
- \right)\\
- \\
&=& \left(
- \begin{array}{c}
- - \nu\Delta\delta \mathbf{u}^{k} + \mathbf{u}^{k}\cdot\nabla\delta\mathbf{u}^{k}+\delta\mathbf{u}^{k}\cdot\nabla\mathbf{u}^{k}+ \nabla\delta p^{k}\\
- - \nabla \cdot\delta \mathbf{u}^{k}\\
- \end{array}
- \right).
+ \begin{array}{c}
+ - \nu \Delta \delta \mathbf{u}^{k}
+ + \mathbf{u}^{k} \cdot \nabla \delta \mathbf{u}^{k}
+ + \delta \mathbf{u}^{k} \cdot \nabla \mathbf{u}^{k}
+ + \nabla\delta p^{k}\\
+ - \nabla \cdot \delta \mathbf{u}^{k}\\
+ \end{array}
+ \right).
@f}
Therefore, we arrive at the linearized system:
@f{eqnarray*}
-- \nu\Delta\delta\mathbf{u}^{k} + \mathbf{u}^{k}\cdot\nabla\delta\mathbf{u}^{k}+\delta\mathbf{u}^{k}\cdot\nabla\mathbf{u}^{k}+ \nabla\delta p^{k} = \mathbf{g}, \\
-- \nabla \cdot\delta \mathbf{u}^{k} = \nabla\cdot\mathbf{u}^{k},
+ -\nu \Delta \delta \mathbf{u}^{k}
+ + \mathbf{u}^{k} \cdot \nabla \delta \mathbf{u}^{k}
+ + \delta \mathbf{u}^{k} \cdot \nabla \mathbf{u}^{k}
+ + \nabla \delta p^{k}
+ = \mathbf{g}, \\
+ -\nabla \cdot\delta \mathbf{u}^{k}
+ = \nabla \cdot \mathbf{u}^{k},
@f}
-where $\textbf{g} =\textbf{f}+\nu \Delta\textbf{u}^k -(\textbf{u}^k
+where $\textbf{g} =\textbf{f} + \nu \Delta \textbf{u}^k - (\textbf{u}^k
\cdot \nabla)\textbf{u}^k -\nabla p^k$ and $\textbf{u}^k$ and $p^k$ are the solutions from the
previous iteration. Additionally, the
right hand side of the second equation is not zero since the discrete
That is, we first solve a Stokes problem
@f{eqnarray*}
-- \nu_{1} \Delta\textbf{u} + \nabla p &=& \textbf{f}\\
-- \nabla \cdot \textbf{u} &=& 0
+ -\nu_{1} \Delta \textbf{u} + \nabla p &=& \textbf{f}\\
+ -\nabla \cdot \textbf{u} &=& 0
@f}
to get the initial guess for
@f{eqnarray*}
-- \nu_{1} \Delta\textbf{u} + (\textbf{u} \cdot \nabla)\textbf{u} + \nabla p &=& \textbf{f},\\
-- \nabla \cdot \textbf{u} &=& 0,
+ -\nu_{1} \Delta \textbf{u} + (\textbf{u} \cdot \nabla)\textbf{u} + \nabla p &=& \textbf{f},\\
+ -\nabla \cdot \textbf{u} &=& 0,
@f}
which also acts as the initial guess of the continuation method.
Here $\nu_{1}$ is relatively large so that the solution to the Stokes problem with viscosity $\nu_{1}$
Then the solution to
@f{eqnarray*}
-- \nu_{i} \Delta\textbf{u} + (\textbf{u} \cdot \nabla)\textbf{u} + \nabla p &=& \textbf{f},\\
-- \nabla \cdot \textbf{u} &=& 0.
+ -\nu_{i} \Delta \textbf{u} + (\textbf{u} \cdot \nabla)\textbf{u} + \nabla p &=& \textbf{f},\\
+ -\nabla \cdot \textbf{u} &=& 0.
@f}
acts as the initial guess for
@f{eqnarray*}
-- \nu_{i+1} \Delta\textbf{u} + (\textbf{u} \cdot \nabla)\textbf{u} + \nabla p &=& \textbf{f},\\
-- \nabla \cdot \textbf{u} &=& 0.
+ -\nu_{i+1} \Delta \textbf{u} + (\textbf{u} \cdot \nabla)\textbf{u} + \nabla p &=& \textbf{f},\\
+ -\nabla \cdot \textbf{u} &=& 0.
@f}
This process is repeated with a sequence of viscosities $\{\nu_i\}$ that is
$P^{-1}$ as $GP^{-1}y = b$, where
@f{eqnarray*}
-P^{-1} = \left(\begin{array}{cc} \tilde{A} & B^T \\
- 0 & \tilde{S} \end{array}\right)^{-1},
+P^{-1} = \left(
+ \begin{array}{cc}
+ \tilde{A} & B^T \\
+ 0 & \tilde{S}
+ \end{array}
+ \right)^{-1},
@f}
with $\tilde{A} = A + \gamma B^TW^{-1}B$ and $\tilde{S}$ is the
@f{eqnarray*}
P^{-1} =
-\left(\begin{array}{cc} \tilde{A}^{-1} & 0 \\ 0 & I \end{array}\right)
-\left(\begin{array}{cc} I & -B^T \\ 0 & I \end{array}\right)
-\left(\begin{array}{cc} I & 0 \\ 0 & \tilde{S}^{-1} \end{array}\right).
+ \left(
+ \begin{array}{cc}
+ \tilde{A}^{-1} & 0 \\
+ 0 & I
+ \end{array}
+ \right)
+ \left(
+ \begin{array}{cc}
+ I & -B^T \\
+ 0 & I
+ \end{array}
+ \right)
+ \left(
+ \begin{array}{cc}
+ I & 0 \\
+ 0 & \tilde{S}^{-1}
+ \end{array}
+ \right).
@f}
Here two inexact solvers will be needed for $\tilde{A}^{-1}$ and
$f=0$. The boundary condition is
@f{eqnarray*}
-(u(x, y), v(x,y)) &=& (1,0)
- \qquad\qquad \textrm{if}\ y = 1 \\
- (u(x, y), v(x,y)) &=& (0,0)
- \qquad\qquad \textrm{otherwise}.
+ (u(x, y), v(x,y)) &=& (1,0) \qquad\qquad \textrm{if}\ y = 1 \\
+ (u(x, y), v(x,y)) &=& (0,0) \qquad\qquad \textrm{otherwise}.
@f}
When solving this problem, the error consists of the nonlinear error (from